Corruption and the shadow economy: a structural equation model approach - Andreas Buehn; Friedrich G. Schneider (Institute for the Study of Labor (IZA), 2009)
The relationship between corruption and the shadow economy is not clear. Theoretically, they either substitute or complement each other -exhibiting either a negative or positive relationship. This paper -using a structural equation model with two latent variables - extracts information on various dimensions of corruption and the shadow economy to contribute to the debate on their relationship. It presents empirical evidence of a positive relationship between the shadow economy and corruption. The results show that the shadow economy influences corruption more than corruption influences the shadow economy.
urn:nbn:de:101:1-2009061268
Keywords: O17; O5; D78; H11; H26; 330; Shadow economy; corruption; SEM models; Korruption; Schattenwirtschaft; Strukturgleichungsmodell; Schätzung; Welt